The Influence of Transfer Pricing, Profitability, and Earnings Management, with Financial Statement Fraud (Beneish M-Score) as a Moderating Variable on Tax Avoidance: English - Rizal Swan, Achmad; Koenta Adji Koerniawan (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of transfer pricing, profitability, and earnings management on tax avoidance, as well as to illuminate the role of Beneish M-Score as a moderating variable. The study was conducted on companies in the Oil, Gas and Coal Sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The analysis method used is multiple linear regression with a panel data approach. The results of the study indicate that simultaneously, transfer pricing, profitability, and earnings management do not have a significant effect on tax avoidance. Partially, the three independent variables also do not show a significant relationship to tax avoidance. In addition, earnings management proxied through the Beneish M-Score does not have a significant effect on tax avoidance practices. This study also cannot empirically conclude the role of the Beneish M-Score as a moderating variable because no interaction testing was carried out. This finding indicates that tax avoidance is likely more influenced by other factors outside the model, such as ownership structure, corporate governance, or tax regulations. The implications of these results indicate the need for a more comprehensive development model and data-based tax supervision to minimize tax avoidance practices.